Exploring the inhibitory effect and mechanism of 3,4,5-trihydroxybiphenyl on α-glucosidase: an integrated experimental and computational approach - Guo, Ruofan; Yu, Guohua; Li, Yuan; Wang, Youyou; Fan, Huixia; Zhang, Shuo; Wang, Chen; Zhou, Junhui; Yang, Jian; Gao, Feng; Luo, Zhiqiang (Frontiers in Pharmacology, 2025)
3,4,5-Trihydroxybiphenyl (THB) is a naturally occurring compound derived from Sorbus pohuashanensis, primarily reported for its antifungal activity. However, its potential to inhibit α-glucosidase remains unclear. In this study, we assessed the inhibitory effects of THB on α-glucosidase and explored the mechanism of inhibition through kinetic analysis, multispectral techniques, molecular docking and molecular dynamics simulations. Furthermore, a sucrose tolerance test was performed to evaluate the effects of THB on postprandial blood glucose (PBG) levels in mice. The results showed that THB exhibited a non-competitive and reversible inhibitory effect on α-glucosidase, with IC50, Km, and Ki values of 11.52 μM, 0.69 ± 0.02 mM, and 26.26 ± 4.95 μM, respectively. THB showed a good affinity for α-glucosidase, with a KD value of 3.91 × 10−5 M. The interaction between THB and α-glucosidase induced significant changes in the enzyme’s microenvironment and secondary structure. The primary driving force for the binding of THB to α-glucosidase was hydrogen bonding. Additionally, THB could significantly reduce PBG levels in mice. Collectively, these findings suggest that THB holds potential as a natural inhibitor for the development of α-glucosidase-targeting agents.